Dyslipidemia and Hypertension Among Type 2 Diabetics at a Tertiary Care Hospital of South Gujarat, India - Jash Kotak; Kirtida Tandel; Mithil Kotak; Diwakar Sharma (Healthline)
Introduction: The number of diabetes cases are rising globally along with comorbidities like hypertension and dyslipidemia. Objectives: To estimate the prevalence of dyslipidemia and hypertension in type 2 diabetes (T2DM) patients of Valsad, Gujarat, India. Methods: This is a cross-sectional study of total 62 blood samples of T2DM patients selected by convenience sampling which analysed fasting blood sugar (FBS), postprandial blood sugar (PP2BS), cholesterol, triglyceride (TG) and high-density lipoprotein (HDL) using standard methods at a tertiary care hospital of Valsad. Low density lipoprotein (LDL) and very low-density lipoprotein (VLDL) were also estimated using Martin-Hopkins and Friedewald equations respectively. Results: In study participants, 11.29% had neither hypertension (HTN) nor dyslipidemia, 64.52% had HTN, 77.42% had dyslipidemia and 53.22% patients had HTN and dyslipidemia along with diabetes. Conclusion: Results suggest a high prevalence of dyslipidemia and HTN in study subjects. Early screening and administration of lipid-lowering agents are required in these patients.